Systematic review of empirical research on technology-enhanced distance laboratory education after the COVID-19 pandemic - Gyeong-Geon Lee; Wonhyeong Jang (Educational Technology & Society, 2024)
This study conceptualized Technology-Enhanced Distance Laboratory (TEDL) as a subset of Non-Traditional Laboratory (NTL) to best describe global STEM education practices after the COVID-19 pandemic. We systematically gathered and examined 141 empirical TEDL studies reported from March 2020 to August 2022. Most studies were contextually rooted in higher education, with a frequent focus on subjects such as Chemistry, Medical/Veterinary/Pharmacy/Nursing, and Electrical/Computer Engineering. The studies predominantly employed technologies such as video, simulations, web/apps, remote control, and virtual reality. Temporally, the majority of the studies utilized media responsive to student manipulation, with participant interaction predominantly synchronous. Spatially, most studies facilitated home-based learning. Data collection in most studies was quantitative, employing survey/questionnaire and/or quiz/exam. As a consequence of TEDL implementation after the COVID-19, many studies posited it positively impacted student learning. However, only about a half of the studies scrutinized the effectiveness of TEDL against comparison group(s). Moreover, the measured learning outcomes tended to favor student “perceptions” and “knowledge & understanding.” This review provides valuable insights into empirical TEDL studies and proposes future research topics that contribute to the evolution of post-COVID-19 STEM laboratory education research and practice.